A secularização segundo Peter L. Berger e Rodney Stark/William Sims Bainbridge - Provenzi, Anoar Jarbas (2013)
This study is about the secularization according to Peter L. Berger (theory of secularization) and according to Rodney Stark/William Sims Bainbridge (rational choice theory). Berger (chapter 1) affirms in Sacred Canopy the decrease of religion in modernity, whereas Stark/Bainbridge (chapter 2) supports in A theory of religion its increasing or maintenance. However, both theories have problems (chapter 3). Berger is criticized to affirm the equivalence between modernity and secularization, the belief in a previous age of the faith and the necessity of religious monopoly; Stark/Bainbridge are criticized to defend previous power of rational choice theory, a decontextualized universal rationality and an merely economic approach of religious phenomenon